2003
DOI: 10.1128/jvi.77.22.11882-11895.2003
|View full text |Cite|
|
Sign up to set email alerts
|

PPPYEPTAP Motif Is the Late Domain of Human T-Cell Leukemia Virus Type 1 Gag and Mediates Its Functional Interaction with Cellular Proteins Nedd4 and Tsg101

Abstract: The human T-cell leukemia virus type 1 (HTLV-1) Gag polyprotein contains two adjacent proline-rich motifs (sequence PPPYEPTAP) in the C terminus of the matrix domain. Proline-to-alanine mutations were introduced into either or both motifs of HTLV-1 to determine the effect on the release of HTLV-1 virus-like particles from 293T cells. The release of both single mutants was significantly reduced, whereas a double mutation in both motifs abolished the release of the HTLV-1 particles. Two-hybrid and in vitro bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 67 publications
4
74
2
Order By: Relevance
“…It has been recently suggested that Tsg101 and Nedd4 might respectively act at an early and late stage of HTLV-1 budding (Bouamr et al, 2003). Our data clearly support the opposite model as we obtained strong evidence that HTLV-1 Gag encounters Nedd4.1 before Tsg101.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…It has been recently suggested that Tsg101 and Nedd4 might respectively act at an early and late stage of HTLV-1 budding (Bouamr et al, 2003). Our data clearly support the opposite model as we obtained strong evidence that HTLV-1 Gag encounters Nedd4.1 before Tsg101.…”
Section: Discussionsupporting
confidence: 81%
“…By depleting Tsg101 in HTLV-1-producing cells, we demonstrated that this protein is also necessary for HTLV-1 release. Consistently, HTLV-1 Gag is able to associate with Tsg101 in vitro (Bouamr et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this model, the viral protein Gag is the equivalent of the late endosomal cargo and different L-domains recruit the ESCRT proteins through the interaction with different cellular adaptor proteins. It is widely accepted that PTAP motifs recruit the ESCRT-I complex trough the interaction with TSG101 (28,35,36), whereas PPXY motifs utilize a subset of HECT ubiquitin ligases to facilitate viral budding (23,(37)(38)(39). A third type of L-domain containing the LYPXL motif recruits the ESCRT machinery by interacting with AIP1/ALIX (6, 7), the human homologue of Bro1.…”
Section: Interaction Of Amsh With the Class E Vps Pathway-basedmentioning
confidence: 99%
“…Further analysis revealed that Nedd4 was expressed at various levels in several embryonic and adult tissues (42). Nedd4 is the prototypical member of the Nedd4 ubiquitin ligase family and regulates diverse cellular processes including signal transduction (which is involved in cancer development [10,49,73,75]), protein trafficking (52, 63), and viral budding (6,23,36,60,71,80).…”
mentioning
confidence: 99%